Pengaruh Sales Growth, Koneksi Politik, Good Corporate Governance dan Investment Opportunity Set Terhadap Tax Avoidance: Studi pada Perusahaan Manufaktur Sub Sektor Industri Dasar dan Kimia Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023 - Ida Ayu Mirah Dwi Sasmitha; I Ketut Jati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Taxes are one of the largest state revenues in the state budget and have a major contribution to economic growth and play an important role in maintaining public welfare. The purpose of this study is to empirically examine the effect of sales growth, political connections, board of commissioners, institutional ownership, audit committee, audit quality and investment opportunity set on tax avoidance in manufacturing companies in the basic and chemical industry sub-sectors for the 2021-2023 period. The population in this study were all manufacturing companies in the basic and chemical industry sub-sectors listed on the Indonesia Stock Exchange for the period 2021-2023, the sampling technique in the study, namely purposive sampling technique so that 123 observational samples were obtained. The results of this study found that sales growth, institutional ownership and audit committee have a negative and significant effect on tax avoidance. Political connections have a positive and significant effect on tax avoidance, while the board of commissioners, audit quality and investment opportunity set have no effect on tax avoidance. The implication of this research for business practices and investors is referring to the research results that the variables of sales growth, institutional ownership, audit committee and political connections have an influence on tax avoidance. The practical implications of this research provide that interested parties can make wiser and more informative decisions, which not only consider potential financial benefits but also risks related to corporate governance and reputation.